Defect Reduction in Tempe Production Using SPC and FMEA Methods - Hadinugraha, Aditya Shafa; Jazuli, A Muhammad (Jurnal Management Risiko dan Keuangan, 2025)
This study aims to analyze quality control of Omah Tempe's tempe production using Statistical Process Control (SPC) and evaluate improvement actions through Failure Mode and Effect Analysis (FMEA). A descriptive quantitative approach was employed, using the total production of tempe from December 27, 2024, to January 26, 2025. Data were collected through observation, interviews, and documentation. Four SPC tools: Check Sheet, Control Chart, Pareto Diagram, and Cause and Effect Diagram were used to identify defect types and causes. FMEA was applied to prioritize corrective actions using the Risk Priority Number (RPN). The study found thirtheen causes of defects, including limited workforce, unhygienic worker behavior, weak supervision, inconsistent fermentation, raw material issues. Based on the findings, Omah Tempe is suggested to increase workforce, conducting daily evaluations, improving sanitation, using checklists and thermometers, selecting higher quality raw materials, and providing guidance to reduce human error. The implications of this study highlight the importance of enhancing quality control at every stage of tempe production. Consistent quality supervision and improved raw material selection are need to reduce defects and enhance tempe production.